Computer-aided Construction Engineering Management Evaluation Based on Chaotic Optimization Algorithm. (April 2020) - Ge, Fan
Abstract: With the continuous acceleration of economic development and the improvement of urbanization, people have a higher and higher demand for better living and working environments. The quality and safety of buildings have become the focus of people's attention. For the computer-aided construction engineering projects, engineering quality is the priority, which requires the full attention of the building, supervision, and construction units to ensure the total quality of the computer-aided construction project.